2014
DOI: 10.1177/1753193414529046
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid scaffold for skin defects in congenital syndactyly release surgery: a novel technique based on the regenerative model

Abstract: Syndactyly release may require skin grafting to fill the skin defects, which might lead to complications or poor cosmetic outcomes. A simple graftless technique for syndactyly release with a hyaluronic acid (HA) scaffold used to cover the bare areas is described. Between 2008 and 2011, release of 26 webs in 23 patients was performed. All skin defects were covered with Hyalomatrix(®) PA. One patient was excluded due to early post-operative infection that required HA scaffold removal before its integration. Web … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Mechanical damage to articular cartilage modulates lubricin biosynthesis. [116] HA has also been used as a nanoparticle delivery vehicle for drugs, RNA, DNA, and growth factors. [98] In mice lacking PRG4 a loss of articular cartilage structure, stiffness, and boundary lubrication severely depressed the articulatory properties of murine knee joints.…”
Section: Functional Organization Of Articular Cartilagementioning
confidence: 99%
“…Mechanical damage to articular cartilage modulates lubricin biosynthesis. [116] HA has also been used as a nanoparticle delivery vehicle for drugs, RNA, DNA, and growth factors. [98] In mice lacking PRG4 a loss of articular cartilage structure, stiffness, and boundary lubrication severely depressed the articulatory properties of murine knee joints.…”
Section: Functional Organization Of Articular Cartilagementioning
confidence: 99%
“…A high level of satisfaction with the appearance of the facial skin after tear trough and temporal fossa augmentation was noted by Tung et al, and Berguiga et al 32,33 Jegasothy et al, 34 also reported beneficial effects (wrinkle depth reduction, improved skin hydration, firmness and elasticity) of low molecular nano-hyaluronic acid injections. Positive changes in the appearance of the facial skin after HA treatment (improved firmness and pigmentation) were observed by Landi et al 35 Trong et al 36 also documented improved skin elasticity and wrinkle depth reduction, while Baspeyras et al, 37 observed significant improvement in skin hydration, firmness and viscoelasticity after HA microinjection treatment. A statistically significantly improved radiance, pigmentation and hydration were observed by Sparavigna et al, 38 in the process of treating skin with symptoms of ageing and photoaging.…”
Section: Discussionmentioning
confidence: 84%
“…In addition, Hyalograft 3D™ is composed by seeding autologous fibroblasts cultured over a 3D hyaluronic acid‐derived scaffold, named Hyalomatrix ® . Hyalomatrix ® consists of a bilayer composed by an outer silicone membrane that acts as a temporary epidermal barrier, and an internal hyaluronan scaffold . The TISSUEtech Autograft System™ represents a good attempt to biomimic the histology of the human skin and has also shown to be well tolerated whilst being able to heal diabetic ulcers and pressure wounds in 1 year or less …”
Section: Cellular Substitutesmentioning
confidence: 99%
“…Hyalomatrix â consists of a bilayer composed by an outer silicone membrane that acts as a temporary epidermal barrier, and an internal hyaluronan scaffold. [34][35][36] The TISSUEtech Autograft System TM represents a good attempt to biomimic the histology of the human skin and has also shown to be well tolerated whilst being able to heal diabetic ulcers and pressure wounds in 1 year or less. 33 Nowadays other skin substitutes made of synthetic polymers, such as PLGA, polycaprolactone, or polypyrrole, are being investigated to generate membranes as platforms to seed fibroblasts.…”
Section: Cellular Substitutesmentioning
confidence: 99%